Formulation of a Functional Probiotic Beverage Using Maesil (Prunus mume) Syrup By-Product Fermented by Lactiplantibacillus plantarum KFOM 0042 - Chan-Il Bae; Yoon-Soo Gwak; Dasol Nam; Tae Gyu Nam; Hyun-Seok Kim; Mi-Ju Kim (Fermentation)
Maesil (Prunus mume) syrup is the most common form of maesil consumption in Korea; however, its production generates large quantities of by-products. This study aimed to develop a functional probiotic beverage through the lactic acid fermentation of maesil syrup by-products (MSBs). To optimize fermentation, eight strains of Lactiplantibacillus plantarum were tested, and KFOM 0042 was selected based on its superior acid production in MSBs. The effects of MSB concentration (5%, 10%, 15%, or 20%), pH levels (3, 4, or 5), and sugar type (none, glucose, fructose, or sucrose) were evaluated. The optimal conditions were found to be 20% MSB at pH 4 or 5, either without added sugar or with sucrose. After fermenting under these conditions for 4 days, the probiotic beverages were stored at 4 °C for 30 days to assess stability. All formulations maintained LAB counts above 7 log CFU/mL for 18 days, but only the beverage with sucrose sustained these levels for 25 days. Additionally, antioxidant activity, total polyphenol, and flavonoid content increased post-fermentation, with the highest lactic acid levels observed at pH 5. Overall, this study presents a novel strategy for upcycling MSB into a probiotic beverage with enhanced functional and microbial stability.